Rancang Bangun Sistem Monitoring Pengaduan dan Pelaporan Pada Desa Berbasis Web - Rifaldi, Muhammad; Fitriani, Leni (Institut Teknologi Garut, 2025)
The advancement of digital technology in the era of the Industrial Revolution 4.0 opens up opportunities for village governments to improve the quality of public services. This research aims to design and build a web-based complaint monitoring and reporting system, with implementation in the Village, Garut Regency. The developed system, E-LaporDesa, uses the Rational Unified Process (RUP) method which includes the Inception, Elaboration, Construction, and Transition stages. The system integrates a Geographic Information System (GIS) to visualize data to support data-based decision-making. The main features of E-LaporDesa include location-based reporting, continuous monitoring, and comprehensive data management. Testing was conducted through blackbox testing to ensure system functions run according to specifications, as well as beta testing with end users to obtain feedback before publication. The results showed that this system can improve the responsiveness of village government services. The implementation of E-LaporDesa is expected to be a model that can be replicated and adapted to the needs of other villages to improve the effectiveness of complaints management and digital-based public services.